2019
DOI: 10.1507/endocrj.ej18-0542
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course and potential underlying mechanisms of everolimus-induced hyperglycemia

Abstract: The mechanistic target of rapamycin (mTOR) inhibitor everolimus is an antitumor agent known to cause hyperglycemia. However, the clinical course of everolimus-induced hyperglycemia, its pathophysiological basis, and the treatment strategy are not clear. In this case series report, we present the clinical course of everolimus-induced hyperglycemia in four patients. Hyperglycemia occurred 3-8 weeks after the administration of everolimus irrespective of the body mass index (range, 21.3-29.1 kg/m 2) or pre-existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…mTOR inhibitor may increase the fasting glucose level, contributing to type 2 DM pathogenesis by alleviating glucose tolerance 10,14,44 . According to evidence on everolimus in breast cancer, hyperglycemia is one of the most common high‐grade adverse events, 20 moreover, everolimus induced hyperglycemia by increasing basal hepatic glucose production in diabetic and nondiabetic patients 45 . Our findings for everolimus‐treated obese mice are consistent with previous findings regarding the exacerbation of glucose intolerance.…”
Section: Discussionsupporting
confidence: 89%
“…mTOR inhibitor may increase the fasting glucose level, contributing to type 2 DM pathogenesis by alleviating glucose tolerance 10,14,44 . According to evidence on everolimus in breast cancer, hyperglycemia is one of the most common high‐grade adverse events, 20 moreover, everolimus induced hyperglycemia by increasing basal hepatic glucose production in diabetic and nondiabetic patients 45 . Our findings for everolimus‐treated obese mice are consistent with previous findings regarding the exacerbation of glucose intolerance.…”
Section: Discussionsupporting
confidence: 89%
“…In some cancer patients, high doses of rapamycin or everolimus can cause hyperglycemia, which is usually mild (grade 1-2) and reversible, and does not lead to treatment interruption [8789]. Hyperglycemia is a common side effect of many oncotargeted drugs and is not a manifestation of diabetes.…”
Section: Metabolic Effects or Rapamycin And Starvationmentioning
confidence: 99%
“…Hyperglycemia is a common side effect of many oncotargeted drugs and is not a manifestation of diabetes. Everolumus, for example, can cause hyperglycemia by decreasing insulin production [89].…”
Section: Metabolic Effects or Rapamycin And Starvationmentioning
confidence: 99%
“…In a human study, however, a pan-mTOR inhibitor did not cause hyperglycemia 9 . Furthermore, a mechanistic study in humans showed that prolonged treatment with rapamycin causes hyperglycemia by decreasing insulin production 130 , and insulin production depends on mTORC1. Thus, inhibition of mTORC2 by rapamycin has not yet been proved in humans.…”
Section: Benevolent Insulin Resistance With Low Mtor Activitymentioning
confidence: 99%